Macrogonadotropinoma, a venous thromboembolic event and asymptomatic extensive periventricular white matter changes in a patient with Klinefelter syndrome. Issue 4 (4th March 2020) - Namboodiri, Divya; Ng, Hui Yi; Zala, Aakansha; Magnussen, John; Davidson, Andrew; Champion, Bernard; Preda, Veronica
Abstract: Gonadotropinoma in Klinefelter syndrome (KS) is uncommon and may be a result of protracted stimulation of gonadotrophs from lack of androgen feedback. Associations of white matter changes and increased venous thromboembolic risk have been reported and need to be considered in patients with KS. Abstract : Gonadotropinoma in Klinefelter syndrome (KS) is uncommon and may be a result of protracted stimulation of gonadotrophs from lack of androgen feedback. Associations of white matter changes and increased venous thromboembolic risk have been reported and need to be considered in patients with KS.